Question
upstudy study bank question image url

20) \( 6^{-2 n-3}=216 \)

Ask by Johnston Greene. in the United States
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

\( n = -3 \)

Solution

To solve the equation \( 6^{-2n - 3} = 216 \) for \( n \), follow these steps: 1. **Recognize the Base and Exponent:** The equation involves exponentials with base 6. Notice that \( 216 \) is a power of 6: \[ 6^3 = 6 \times 6 \times 6 = 216 \] 2. **Rewrite the Equation with the Same Base:** Replace \( 216 \) with \( 6^3 \): \[ 6^{-2n - 3} = 6^3 \] 3. **Set the Exponents Equal:** Since the bases are the same and the equation holds true, their exponents must be equal: \[ -2n - 3 = 3 \] 4. **Solve for \( n \):** - Add 3 to both sides to isolate the term with \( n \): \[ -2n = 3 + 3 \\ -2n = 6 \] - Divide both sides by -2 to solve for \( n \): \[ n = \frac{6}{-2} \\ n = -3 \] **Final Answer:** \[ n = -3 \]

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

The Deep Dive

To solve the equation \( 6^{-2n-3} = 216 \), first express 216 as a power of 6. Since \( 6^3 = 216 \), we can rewrite the equation as \( 6^{-2n-3} = 6^3 \). This means the exponents must be equal, so we set up the equation: \[ -2n - 3 = 3 \] Now, add 3 to both sides: \[ -2n = 6 \] Then, divide by -2: \[ n = -3 \] Therefore, the solution is \( n = -3 \).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy